You are on page 1of 4

2006-2005

2 8
4

=C

2 22 2
4
2 2 2
=
4
=

A = 2 18

48
3

= 2 32 2
2

4 3
3
2

= 2 3 2

)( 2

=B

= 3

)( 2

4
2 2
=
4
4
=
4
=1

4 3
3
=4
=

= 3 2
=6

E = 4 + 15 4 15

D = 5 27 4 48 + 2 3
= 5 32 3 4 42 3 + 2 3

()

(4 +

( 4)

15 4 15
2

= 15 3 16 3 + 2 3

) (
15

= 16 15

= (15 16 + 2 ) 3

= 1
=1

(1- x

( 5 x + 4 )( x + 1) + x 2 1 = 0 ( 5 x + 4 )( x + 1) + ( x 1)( x + 1) = 0
( x + 1) ( 5 x + 4 ) + ( x 1) = 0
( x + 1) [ 6 x + 3] = 0
( x + 1) = 0 ( 6 x + 3) = 0

http://mowahad.blogspot.com

1
x = 1
2

.............. x =

2 x 3 ( x + 1) 3 x
x x +1 1 x

: = +

= +
6
6
6 6
3
2
2 6
2 x 3 ( x + 1) = 3 + x

- x

2 x 3 x x = 3 + 3
2 x = 6
................................... x = 3

(2
- x

: 5 x 3

) 2 ( x + 3 3 6

2x 5x

3 x 9
.............. x 3

2 ( 2 x + 5 ) 5 x 8
2 x + 5 5 x 8

4
4
2
4
2 ( 2 x + 5 ) 5 x 8

- x

4 x + 5 x 8 10
9 x 18
................ x 2

(1
5 a 2 2 2b 6 5 + 2 a + 2b 2 + 6 3 a + 2b 4
5 a 2 3 b 1 5 3 a b 2 1 8 a b 3
2 a 5 1 b 3 2 a b 15 15 a b 2
(2
c c 3

1
1
2
1
6 c 3

1 c 2 3 6 4 c 2 9 2 c 3

(1
) ( EF ) ( BC ) ( AC ) ( AB
AF AE
=
AB AC

)(1

http://mowahad.blogspot.com

) ( GE ) ( DC
AG AE
=
AD AC
(2

)( 2

AF AG
=
) (1 ) ( 2
AB AD

(1
2

)( 6

AB 2 + AC 2 = 22 +

= 4+6
= 10

-
2

) ( 10

= BC 2
ABC . A
-
AB
2
10
= cos B
=
=
BC
5
10

6
15
AC
=
=
5
BC
10

sin B

15
6
=
2
10

= sin B

= tan B

cos B

- AEB E :

15
AE
AE = AB sin B = 2
= sin B
5
AB

10
BE
BE = AB cos B = 2
= cos B
5
AB
(2

) ( AC ) ( AD

31 + 59 = 90
53 + 37 = 90

(1

http://mowahad.blogspot.com

) ( BD ) // ( FG

1
BOH
2

1
BDH BOH = 60
2
= 30

= BDH

(2
] [ AB D ADB D

1
ADB = 90 ADB
3

http://mowahad.blogspot.com

= BDH